텍스트마이닝을 활용한 HPV 백신 접종 관련 연구 동향 분석 - 손예동; 강희선; Son, Yedong; Kang, Hee Sun (Child health nursing research, 2019)
Purpose: The purpose of this study was to identify human papillomavirus (HPV) vaccination research trends by visualizing a keyword network. Methods: Articles about HPV vaccination were retrieved from the PubMed and Web of Science databases. A total of 1,448 articles published in 2006~2016 were selected. Keywords from the abstracts of these articles were extracted using the text mining program WordStat and standardized for analysis. Sixty-four keywords out of 287 were finally chosen after pruning. Social network analysis using NetMiner was applied to analyze the whole keyword network and the betweenness centrality of the network. Results: According to the results of the social network analysis, the central keywords with high betweenness centrality included "health education", "health personnel", "parents", "uptake", "knowledge", and "health promotion". Conclusion: To increase the uptake of HPV vaccination, health personnel should provide health education and vaccine promotion for parents and adolescents. Using social media, governmental organizations can offer accurate information that is easily accessible. School-based education will also be helpful.